2004
DOI: 10.1017/s0950268804002870
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and source of methicillin-resistant Staphylococcus aureus (MRSA) in the community in Hong Kong

Abstract: SUMMARYAlthough reports of isolation of methicillin-resistant Staphylococcus aureus (MRSA) from patients admitted from the community have increased, few studies have investigated colonization of healthy subjects. This study aimed to determine community levels of MRSA in Hong Kong. Nasal swabs from a cross section of young adults and family units were cultured for MRSA. Antibiotic sensitivities and risk factors for carriage were determined and clonal relationships were investigated by pulsed-field gel electroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 36 publications
3
16
0
1
Order By: Relevance
“…The CAMRSA colonization rate among subjects lacking traditional risk factors was 5.3%, a high rate compared with 0.24% calculated in a meta-analysis (36), 0.6% among children in Chicago (14) in 1999, 3.5% among healthy people in southern Taiwan (19), and 1.4% in Hong Kong (31). It remains to be determined whether this high MRSA colonization rate is widespread in Taipei and other locations in Taiwan or can be found among adults from the same geographic location.…”
Section: Discussionmentioning
confidence: 66%
“…The CAMRSA colonization rate among subjects lacking traditional risk factors was 5.3%, a high rate compared with 0.24% calculated in a meta-analysis (36), 0.6% among children in Chicago (14) in 1999, 3.5% among healthy people in southern Taiwan (19), and 1.4% in Hong Kong (31). It remains to be determined whether this high MRSA colonization rate is widespread in Taipei and other locations in Taiwan or can be found among adults from the same geographic location.…”
Section: Discussionmentioning
confidence: 66%
“…A recent paper by O'Donoghue et al [26] examined the association between previous antibiotic use and MRSA carriage in nasal samples from a group of young adults. The study found no association between MRSA carriage and antibiotic use in the previous 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…This has been a cause of concern particularly as levels of MRSA have continued to increase in the community, most notably in the United States [37] and Australia [38]. Although the prevalence of carriage of CA-MRSA remains low in Hong Kong [6], there is still a need for vigilance as infections with community strains of MRSA have recently occurred [39]. In our study, nasal carriage in dogs was assessed, and it was shown that dogs, in particular those owned by HCWs, can act as an important reservoir of the organism.…”
Section: Discussionmentioning
confidence: 99%
“…Most owners were willing for samples to be collected from both themselves and their dogs, with a small number restricting permission to collection only from their dog. The sample size of 800 was based on a carriage level of 25 % in adult humans [6], and an assumed 25% carriage frequency in dogs belonging to colonized subjects with a 2 % error. For comparison of carriage levels in dogs with limited human contact, 30 stray dogs were sampled for nasal colonization.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation